Perceptions, barriers, and challenges of adopting battery-powered landscape equipment in professional maintenance - Kent, Kati; Brodbeck, Arnold; Hoffman, Mark; Chaves-Cordoba, Bernardo; Bartley, Paul C. (Frontiers in Horticulture, 2025)
Legislative measures and societal pressures are reshaping the landscape maintenance industry by imposing restrictions on gas-powered outdoor power equipment. These regulations are driving a significant shift toward the adoption of eco-friendly alternatives in landscape maintenance practices. To gain insights into the perceptions, benefits, and challenges of adopting battery-powered outdoor power equipment, a survey was conducted among landscape maintenance operators in the USA. Professional landscape companies prioritize operation efficiency factors such as “Reliability” (score of 4.6 out of 5), “Work Capacity” (score of 4.5 out of 5), and equipment “Availability” (score of 4.3 out of 5) rather than the environmental factors such as “Air Pollution” (score of 3.1 out of 5) and “Noise Pollution” (score of 3.2 out of 5) emphasized in recent legislative measures. Of the participants surveyed, 52% said they have integrated battery-powered equipment into their landscape maintenance operations in some capacity. “Noise Pollution” (score of 3.9 out of 5) and “Air Pollution” (score of 3.7 out of 5) were identified as the main drivers behind the integration of battery-powered equipment. “Competitive Advantage” (score of 3.0 out of 5) and “Cost” (score of 2.7 out of 5) were the least motivating factors for battery-powered equipment adoption, suggesting that economic concerns pose a significant barrier to adoption. However, for traditional equipment operators, addressing concerns related to the “Work Capacity, “Power,” and “Quality” of battery-powered equipment could be pivotal in overcoming skepticism. Of traditional gas-powered equipment users, 70% indicated they would consider adopting battery-powered equipment if their concerns were alleviated. Based on these results, future research should aim to fill the existing knowledge gap regarding the long-term operational costs and benefits of battery-powered equipment and gas-powered equipment.